2021
DOI: 10.1680/jgeot.19.p.329
|View full text |Cite
|
Sign up to set email alerts
|

Influence of failure mechanism on seismic bearing capacity factors for shallow foundations near slopes

Abstract: The bearing capacity of shallow foundations may decrease when located near slopes, particularly under seismic conditions. However, there is limited work that isolates the destabilising influences of seismicity and finite slope geometry on ultimate bearing capacity in terms of conventional bearing capacity factors. Herein, analytical solutions based on upper-bound kinematic limit analysis are used to isolate both the mechanism of failure and bearing capacity factors (Nc, Nγ and Nq) for shallow foundations near … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…e pseudostatic (PS) approach is a widely adopted and accepted technique in engineering practice and has been employed to investigate the earthquake effects on rock slope stability [30][31][32][33][34][35][36][37]. Based on the PS method, Li et al [25] first used the limit analysis method (LAM) to develop the stability charts for seismic stability assessment of the rock slopes directly based on the HB failure criterion.…”
Section: Review Of Existing Stability Charts For Rock Slopes Based On the Hb Criterionmentioning
confidence: 99%
“…e pseudostatic (PS) approach is a widely adopted and accepted technique in engineering practice and has been employed to investigate the earthquake effects on rock slope stability [30][31][32][33][34][35][36][37]. Based on the PS method, Li et al [25] first used the limit analysis method (LAM) to develop the stability charts for seismic stability assessment of the rock slopes directly based on the HB failure criterion.…”
Section: Review Of Existing Stability Charts For Rock Slopes Based On the Hb Criterionmentioning
confidence: 99%
“…In the common analysis methods and design standards for slope and foundation stability problems, the soil shear strength is generally represented in the type of the linear Mohr-Coulomb (MC) strength envelope (e.g., Chen [1], Michalowski and Drescher [2], Gao et al [3], Rao et al [4], Yang et al [5], and Ye et al [6,7]). Whereas, a number of experimental studies [8][9][10][11][12][13] have revealed that the shear strength envelopes for almost all geomaterials are nonlinear, particularly in low normal stress range, which is commonly relevant to the stress distribution on sliding surfaces of instable slopes.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above analysis, the purpose of this paper is to extend the UBLA method of slope stability with tension crack by Michalowski [5] and Utili and Abd [11] into slopes reinforced with prestressed anchor cables and seismic condition. A rotational failure mechanism (log-spiral surface) was considered to find the critical results [4,[31][32][33][34]. By comparison and analysis of existing slope examples, the correctness and feasibility of the proposed UBLA method have been verified.…”
Section: Introductionmentioning
confidence: 99%